Respuestas

2012-08-09T01:16:46+02:00

Potencia de x.

xn dx = x(n+1) / (n+1) + C (n  -1)  
Demostración 1/x dx dx = ln|x| + C

Exponente / Logaritmo

ex dx = ex + C  
Demostración  bx dx = bx / ln(b) + C  
Demostración ln(x) dx = x ln(x) - x + C 
Demostración  

Trigonométrica

sen x dx = -cos x + C  
Demostración cos x dx = sen x + C  
Demostración tan x dx = -ln|cos x| + C 
Demostración csc x dx = - ln|csc x + cot x| + C sec x dx = ln|sec x + tan x| + C cot x dx = ln|sen x| + C

Resuelta Trigonométrica

cos x dx = sen x + C  
Demostración sen x dx = -cos x + C  
Demostración sec2 x dx = tan x + C  
Demostración csc x cot x dx = -csc x + C  
Demostración sec x tan x dx = sec x + C  
Demostración csc2 x dx = -cot x + C  
Demostración

Trigonométrica Inversa

arcsen x dx = 1 (1-x2) + C   arccsc x dx = -1|x|(x2-1) + C   arccos x dx = -1 (1-x2) + C   arcsec x dx = 1 |x|(x2-1) + C   arctan x dx = 11+x2 + C   arccot x dx = -11+x2 + C  

Hyperbólica

senh x dx = cosh x + C cosh x dx = senh x + C tanh x dx = ln( cosh x ) + C csch x dx = ln( tanh(x/2) ) + C sech x dx = atan( senh x ) + C coth(x) dx = ln( senh x ) + C

Presione la Demostración para ver una demostración/discusión del teorema.